UPAYA HUKUM KONSUMEN JAMAAH UMRAH DALAM SENGKETA WANPRESTASI TRAVEL PENYELENGGARA PERJALANAN IBADAH UMROH(PPIU) - Fahrul Rizal; Syaipul Puad Tarigan; Ismayani Ismayani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Reality shows the existence of default practices, namely the failure of Umrah travel organizers to fulfill their obligations to the congregation according to the agreed contract. Cases such as the failure of the congregation's departure, fraud and embezzlement of funds by Umrah travel, especially those that have become public spotlight that have harmed tens of thousands of prospective pilgrims materially and immaterially, show the low level of legal certainty regarding the rights of victims. The formulation of the problem of this research is How are the regulations for consumers of Umrah pilgrims in default disputes between Umrah pilgrimage travel organizers (PPIU)? What form is taken for consumers of Umrah pilgrims in default disputes between Umrah pilgrimage travel organizers (PPIU)? In collecting data to be compiled in the research, the author uses a data collection method through library research. In this library study the author obtains the necessary materials by studying books, writings and legal products related to the main problem. Regulations for Umrah pilgrim consumers regarding disputes over breaches of contract with Umrah pilgrimage travel agents (PPIU) should be submitted to the Ministry of Religious Affairs, the institution authorized to supervise, prosecute, and revoke the permits of Umrah pilgrimage travel agencies. Based on Minister of Religious Affairs Regulation Number 8 of 2018 concerning the Organization of Umrah Pilgrimage Travel, specifically Article 41, it is stated that agencies that violate their obligations, such as neglecting pilgrims or failing to depart, may be subject to administrative sanctions in the form of revocation of their operational permits. Forms of legal protection for Umrah pilgrim consumers regarding disputes over breaches of contract with Umrah pilgrim travel agents (PPIU). Preventive legal protection is an effort to prevent violations or losses for prospective pilgrims, while repressive legal protection is a form of response to rights violations and aims to provide compensation or restitution to the injured party. Both play a crucial role in creating a safe and accountable Umrah pilgrimage ecosystem. Unfortunately, in practice, preventive legal protection remains formalistic. Keywords: Consumers; Pilgrims; Default.   Abstrak: Realitas menunjukkan adanya praktik wanprestasi, yaitu kegagalan penyelenggara travel umroh dalam memenuhi kewajibannya kepada jamaah sesuai kontrak yang telah disepakati. Kasus-kasus seperti kegagalan pemberangkatan jamaah, penipuan dan penggelapan dana oleh travel umroh, khususnya yang menjadi sorotan publik yang merugikan puluhan ribu calon jamaah secara material dan immaterial, menunjukkan rendahnya tingkat kepastian hukum terhadap hak korban. Perumusan masalah penelitian ini adalah Bagaimana pengaturan terhadap konsumen jamaah umrah sengketa wanprestasi travel penyelenggara perjalanan ibadah umroh (PPIU)? Bagaimana bentuk terhadap konsumen jamaah umrah sengketa wanprestasi travel penyelenggara perjalanan ibadah umroh (PPIU)?? Dalam mengumpulkan data-data yang akan disusun dalam penelitian, penulis mempergunakan metode pengumpulan data secara studi kepustakaan atau library resecrh. Dalam studi kepustakaan ini penulis mendapatkan bahan-bahan yang dibutuhkan dengan jalan mempelajari buku-buku, tulisan-tulisan dan produkproduk undang-undang yang ada kaitannya dengan pokok permasalahan. Pengaturan terhadap konsumen jamaah umrah sengketa wanprestasi travel penyelenggara perjalanan ibadah umroh (PPIU) pengaduan kepada Kementerian Agama, sebagai institusi yang memiliki kewenangan untuk mengawasi, menindak, dan mencabut izin biro perjalanan ibadah umrah. Berdasarkan Peraturan Menteri Agama Nomor 8 Tahun 2018 tentang Penyelenggaraan Perjalanan Ibadah Umrah, khususnya Pasal 41 disebutkan bahwa biro yang melanggar kewajiban seperti menelantarkan jemaah atau gagal memberangkatkan, dapat dikenai sanksi administratif berupa pencabutan izin operasional. Bentuk terhadap konsumen jamaah umrah sengketa wanprestasi travel penyelenggara perjalanan ibadah umroh (PPIU) Perlindungan hukum preventif merupakan upaya untuk mencegah timbulnya pelanggaran atau kerugian bagi calon jemaah, sedangkan perlindungan hukum represif merupakan bentuk reaksi terhadap terjadinya pelanggaran hak dan bertujuan untuk memberikan ganti rugi atau pemulihan kepada pihak yang dirugikan. Keduanya memiliki peran penting dalam menciptakan ekosistem penyelenggaraan ibadah umrah yang aman dan akuntabel. Sayangnya, dalam praktik perlindungan hukum preventif masih bersifat formalistik. Kata Kunci: Konsumen; Jamaah; Wanprestasi.